Social innovation as a multidimensional phenomenon: An analysis of demands in the context of Sustainable Development (Research, Society and Development, 2019)
The expansion of capitalism led to an intensification of problems, mainly of a social nature, which led to degrading processes of exploitation and exclusion of large human contingencies, depriving individuals of basic capacities and fundamental rights. Among these problems we can highlight social inequality, which is perceived through the exponential increase of differences between classes, lack of access to quality education and difficulty access to basic services, also triggered by this lack of human capacity due to absences of freedoms policies, economic facilities, social opportunities, guarantees of transparency and protective security. The objective of this work is to raise demands for social innovation in the city of Sousa, Paraíba. This is an exploratory, descriptive, qualitative research, carried out through a questionnaire composed of 20 objective questions, based on the categories Health, Income / Labor and Education, addressed by the HDI, applied in a sample of 371 Bolsa Família recipients, program of the Federal Government. The results obtained reveal several demands in the areas addressed, such as not having outpatient care near family residences, attending the dentist only in cases of need, not having a basic sanitation structure, not having future expectations regarding the labor market, presenting high unemployment, to know children engaged in some work activity, to show interest in entering higher education, showing the social dysfunctions caused by organizational practices, combined with the apparent absence of effective public policies. In conclusion, potential possibilities of developing social innovation were pointed out in consonance with the results obtained.